Role of Men in Teenage Pregnancy in the Bojanala district, North West province, South Africa - Petlele, Rebaone (University of the Witwatersrand, Johannesburg, 2024)
To Professor Odimegwu, words aren’t enough to express my appreciation for your guidance, support and enduring patience. Thank you, Prof, for guiding me through this journey, not only during my PhD, but from my undergraduate years. Thank you for not giving up on me. You have been instrumental in my career progression and achievements. I am most grateful. Dr Mkwananzi, thank you so much for being there for me. You have been my sounding board, you have been rooting for me from day one, thank you for giving of your time, your grace, and all you’ve shared with no reservation…including the laughs. Thank you. To my DPS family, you have been a source of motivation and my constant support system. Thank you to all staff members, past and present. Dr Sasha and Prof Nicole, you have been a constant and positive feature in my academic journey. You have taught me, mentored me and became a great example of what I could achieve. I appreciate you both very much. Ms Gloria, thank you for everything you do. To my fellow PhD brothers and sisters, what an amazing bond we share, thank you for the camaraderie, this journey was so much better with you by my side. You’ve been there and I cannot thank you enough, I know our journey doesn’t end here. To everyone at Community Media Trust (CMT), I am most grateful. Your organisation’s support has been immeasurable. Thuso Molefe, thank you for saying yes, thank you for facilitating all the reinforcement I needed to see through my fieldwork. Boitumelo, ka leboga (thank you) Sistas, your assistance opened so many doors, thank you for all that you did for me and with me. Mam’Wendy, thank you for being there when we needed you. The work you do is a calling, I appreciate all the counsel you provided during this time, not just to my study participants, but those moments I needed to debrief too. I know your work isn’t done yet, thank you for everything. Levite Solomon Mabolawa, you have gone far beyond the call of duty. You were there during all the phases of my fieldwork, you took on multiple roles, you used your resources and time to ensure I achieved what I was there to do. Thank you for being selfless, this would not have been possible without your daily acts of kindness. Thapelo Moloto, you’ve been more than a fellow researcher but a big brother. Thank you for nurturing this process like you would your own. I am so grateful. You never hesitated to take on this task, and I am so happy that it was you who accompanied me on this journey.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy in Demography and Population , In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; men; fathers; teenage pregnancy; contraception decision making; condom use; fertility intensions; fatherhood consequences; Bojanala district; SDG-5: Gender equality